Fontes e doses de nitrogênio em cobertura no feijoeiro de inverno irrigado no sistema plantio direto - da Silva Binotti, Flavio Ferreira; Arf, Orivaldo [UNESP]; Cardoso, Eliana Duarte [UNESP]; de Sa, Marco Eustaquio [UNESP]; Buzetti, Salatier [UNESP]; do Nascimento, Vagner (Universidade Federal de Uberlândia (UFU), 2010)
The common bean is a leguminous of great importance in the Brazilian economy and nitrogen is the taken up nutrient in larger amount. Nitrogen fertilization management is of extreme importance to offer larger economical viability, besides increasing the efficiency of plant in the use of the available resources. The objective this study was to evaluate the effect of sources and doses of sidedressing nitrogen in the development and yield of winter common bean in no tillage system, as well as evaluate its economical viability. A randomized blocks design was used, in a factorial scheme 3x3 with 9 treatments constituted by three sources of nitrogen (ammonium sulphate, urea and ammonium sulphate 1/2 of N + urea 1/2 of N, applied at V(4-3) stadium) and different doses of sidedressing nitrogen (0, 40, 80 kg ha(-1)) in four replications. The study was conducted in Selviria county, MS State in 2004 in no season crop period, in a dystrophic Haplustox soil. The conclusion: independent of nitrogen source, nitrogen fertilization increasing provides increment in yield of winter common bean up to dose 80 kg/ha, and this provides, on average, an increase of 20% in yield compared with control (without sidedressing nitrogen). The urea is the nitrogen source of larger economical efficiency.

O feijoeiro é uma leguminosa de grande importância na economia brasileira, e o nitrogênio é o nutriente absorvido em maior quantidade. O manejo da adubação nitrogenada é de extrema importância no sentido de oferecer maior viabilidade econômica, além de aumentar a eficiência da planta na utilização dos recursos disponíveis. O objetivo do trabalho foi estudar o efeito de fontes e doses de nitrogênio em cobertura no desenvolvimento e produtividade do feijoeiro de inverno no sistema plantio direto, correlacionado com uma análise econômica simples. O delineamento experimental foi de blocos casualizados em esquema fatorial 3x3, constituídos pela combinação de três fontes de nitrogênio (sulfato de amônio, uréia e mistura - sulfato de amônio ½ do N + uréia ½ do N) e diferentes doses de nitrogênio em cobertura (zero, 40 e 80 kg ha-1, aplicado na fase V4-3), com quatro repetições. O projeto foi conduzido no município de Selvíria (MS), no período de outono-inverno de 2004. O solo do local é um LATOSSOLO VERMELHO Distrófico argiloso. Conclui-se que independente da fonte de N, o aumento da adubação nitrogenada proporciona incremento na produtividade do feijoeiro de inverno até a dose de 80 kg ha-1, sendo que esta proporciona em média, aumento de 25 % na produtividade comparado com a testemunha (sem N em cobertura). A uréia é a fonte de nitrogênio de maior eficiência econômica.
Sources and doses of sidedressing nitrogen on irrigated common bean cropped in winter in no tillage system
Keywords: Phaseolus vulgaris L; Nitrogen fertization; Ammonium sulphate; Urea; Economical viability